Preparation and growth mechanism of nickel nanowires under applied magnetic field - Wang, J.; Zhang, L. Y.; Liu, P.; Lan, T. M.; Zhang, J.; Wei, L. M.; Kong, Eric Siu-Wai; Jiang, C. H.; Zhang, Y. F. (Nano-Micro Letters, 2010)
Nickel nanowires with large aspect ratio of up to 300 have been prepared by a hydrazine hydrate reduction method under applied magnetic field. The diameter of nickel nanowires is about 200 nm and length up to 60 μm. The role of magnetic field on the growth of magnetic nanowires is discussed and a magnetic nanowire growth mechanism has been proposed. Nickel ions are firstly reduced to nickel atoms by hydrazine hydrates in a strong alkaline solution and grow into tiny spherical nanoparticles. Then, these magnetic particles will align under a magnetic force and form linear chains. Furthermore, the as-formed chains can enhance the local magnetic field and attract other magnetic particles nearby, resulting finally as linear nanowires. The formation and the size of nanowires depend strongly on the magnitude of applied magnetic field.